2016
DOI: 10.1007/s13205-016-0550-3
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity and oxidative stress perspective of two selected nanoparticles in Brassica juncea

Abstract: This study elaborates the consequences of oxidative stress caused by copper oxide (CuO) and titanium dioxide (TiO2) nanoparticles (NPs) in Brassica juncea. Effect of these two NPs on plant physiology, reactive oxygen scavenging enzyme system (ascorbate peroxidase, catalase, superoxide dismutase), proline content and lipid peroxidation has been estimated in leaves as well as root tissues. Bioaccumulation of NPs has also been evaluated in the current study and the interrelated cascade of the enzymatic system wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(21 citation statements)
references
References 44 publications
(45 reference statements)
1
19
0
Order By: Relevance
“…through the disruption of the electron transport chain, finally resulting in membrane damage through lipid peroxidation, as indicated by increased MDA and lactate dehydrogenase contents [49]. CuNPs have been shown to cause ROS generation leading to membrane lipid peroxidation in several other plant species including Brassica napus [50], Brassica juncea [51], Cucumis sativus [52], Oryza sativa [53] and Coriandrum sativum [54]. Similar results were observed in B. monnieri.…”
Section: Effect Of Cunps On Hydrogen Peroxide and Mda Contents Of B supporting
confidence: 58%
See 1 more Smart Citation
“…through the disruption of the electron transport chain, finally resulting in membrane damage through lipid peroxidation, as indicated by increased MDA and lactate dehydrogenase contents [49]. CuNPs have been shown to cause ROS generation leading to membrane lipid peroxidation in several other plant species including Brassica napus [50], Brassica juncea [51], Cucumis sativus [52], Oryza sativa [53] and Coriandrum sativum [54]. Similar results were observed in B. monnieri.…”
Section: Effect Of Cunps On Hydrogen Peroxide and Mda Contents Of B supporting
confidence: 58%
“…Antioxidant enzymes such as CAT, APX, SOD and glutathione reductase are activated by CuNPs as reported in many plant species such as Brassica napus [50], Brassica juncea [51], Cucumis sativus [52], Oryza sativa [53] and Saccharum officinarum [56]. Zhao et al [57] reported that in Zea mays , expression of genes for antioxidant enzymes, POD 1 and GST 1 increased significantly at a Cu(OH) 2 nanopesticide dose of 10 mg but declined at 100 mg. CATs dismutase H 2 O 2 to H 2 O and O 2 while the SODs catalyse the conversion of superoxides to H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we can conclude that APX activity increased due to plant exposure to TiO 2 -NPs, but in the case of the applied TiO 2 -NPs concentration, only immediately after application. Rao and Shekhawat [ 60 ] used copper oxide and titanium dioxide NPs on Brassica juncea with different concentrations (200–1500 mg·L −1 ). They observed a treatment-dependent increment in APX activity in the roots and shoots of the plant, under the influence of both the nanomaterials; however, the extent of the increase in APX was higher in the copper oxide NPs treatment, compared with titanium dioxide NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Shaw and Hossain (2013) and Hong et al (2015) similar evidence of the increases activity of APX in leaves by the application of nano Cu in Oryza sativa and Lactuca sativa respectively. Rao and Shekhawat (2016); Dimkpa et al (2012) reported that application of nano CuO at the doses of 1000 mg/L and 500 mg/kg gave significantly increase CAT enzymatic activity in Brassica juncea and Triticum aestivum. In addition, Trujillo-Reyes et al (2014) in the root CAT activity was increased with the applied of nano Cu treatment but decrease APX activity in root of Lactuca sativa.…”
Section: Effect Of Cu and Fe Nanoparticles On Enzymatic Activitymentioning
confidence: 99%